An Analysis of Fast Improvement Program of Human Resources for Employee Satisfaction of PT. PLN (Persero), Bandar Lampung Power Sector - Sapmaya Wulan; Kiki Keshia (Bandar Lampung University, 2015)
One thing that should be a concern for companies in order to achieve their goal is to provide job satisfaction to employees. Employees who get job satisfaction will have a greater attachment or commitment and will encourage employees performing better. PT PLN (Persero), Bandar Lampung Power Sector has developed and implemented the Fast Program Improvement of human resource to fulfil employee satisfaction. The formulation of the problem is whether the implementation of the Fast Program Improvement of human resource is able to fulfil employee satisfaction or not. This study used a sample of 33 people is taken randomly with proportional technique. This research also uses descriptive method by means of Conformity Level Analysis and Cartesian diagram with the help of Importance-Performance Analysis. Results of the research showed that the average value of concordance level between the level of interest (job satisfaction desired) and the level of performance of the company (the results of the achievement of Fast Improvement program) are amounted to 81.52% with the category of very fit, but of the 12 attributes there are five attributes which are below average. Results of Importance-Performance Analysis showed that the average value of the level of company performance is amounted to 3.26 < the value of the average interest rate of 4.01. It means that the achievement results of the implementation of Fast Improvement program have not been fully able to meet employee satisfaction. Results of Cartesian diagram analysis shows that there are three attributes in Quadrant A which is not satisfactory and two attributes in Quadrant D is excessive (not effective), 4 attributes in quadrant C is quite satisfactory, and three attributes in quadrant B is very satisfying. It can be concluded that the Fast Improvement program of human resources has not been fully implemented to provide job satisfaction to employees.